Internet of Things (IoT) technology for the implementation of intelligent energy systems. - Adichandra Putra Ariesta, Adichandra Putra Ariesta (Indonesian Journal of Electrical Engineering and Electronics, 2024)
The use of Internet of Things (IoT) technology has become crucial in the advancement of intelligent energy systems amidst global energy transformations. This article discusses the beneficial impacts of integrating the Internet of Things (IoT) in enhancing the efficiency of monitoring, controlling, and making decisions regarding energy management. The Internet of Things, through the use of advanced sensors and connectivity, allows for real-time monitoring, the ability to adapt to changes in demand, and significant improvements in energy efficiency. The study recognises challenges related to security and privacy, but demonstrates that utilising the Internet of Things presents fresh prospects for a more adaptable, efficient, and sustainable energy system. This paper comprehensively examines the important role of the Internet of Things in shaping the future of interconnected and responsive smart energy systems, based on recent literature.